Marine algae from St. Martins Island, Bangladesh. V. Antithamnionella floccosa (Müller) Whittick (Rhodophyceae), a new record - Aziz, Abdul; Islam, A.K.M. Nurul (Bangladesh Journal of Plant Taxonomy, 2008)
Not available. Keywords: Antithamnionella floccosa, Red alga, Rhodophyceae, Marine algae, Bangladesh DOI: 10.3329/bjpt.v15i1.918 Bangladesh J. Plant Taxon. 15(1): 63-65, 2008 (June)